Feasibility Analysis of Sinjai’s Special Minas Beverage Production - Ahmad, Arfandi; Herdianzah, Yan (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2022)
Sinjai Regency is a city that produces many specialty drinks, one of which is Minas (Sinjai Typical Drink) which is a type of fermented drink because it is made from cassava tapai and has a thick yellow texture. This research focuses on the development of the Minas business, which is vulnerable to the risk of rising raw material prices and declining selling prices. The purpose of this research is to do a feasibility study of the Minas business to improve the economy of the people engaged in the business. This study uses a 5 aspect approach, namely, (1) market aspects, (2) technical aspects, (3) management aspects, (4) environmental aspects, (5) socio-economic aspects of culture. The financial aspect of this study shows the PP value for the Sinjai specialty beverage business is 4.63 years, and a positive IRR value of 1.41%, which means that the business is feasible. The Net B/C value of the Minas production business is 4.63. This means that for every Rp. 1 spent  the business will generate a net profit of Rp. 4,63.Keywords : Sinjai specialty drinks, mina's business feasibility, financial aspects, non-financial aspects